Social empowerment of rural women in the Al-Haffa region and its role in development - محمد, نغم; غسان يعقوب,; منذر خدام, (Latakia University Journal -Biological Sciences Series, 2024)
The research aimed to measure the level of social empowerment and human development of rural women in the Al-Haffa region, and to study the relationship between social empowerment and human development. To achieve the research objectives, a random sample of 384 rural women in the Al-Haffa region was taken, and the data necessary for the research was collected by designing a questionnaire designed for this purpose. According to the method of personal interviews with sample members. The descriptive analytical approach was relied upon to analyze and characterize the sample members’ answers to the questionnaire questions using frequency tables and percentages. The quantitative approach was also used to test the research hypotheses using appropriate tests such as the Likert scale and the Spearman correlation coefficient, in addition to using equations to measure the level of development in the region. The percentage of women with secondary, university, and preparatory education was the largest percentage in the sample, while the percentage of illiterate women did not exceed 2.6%, which is a good indicator that reflects the interest in educating rural women in the research area. The average monthly income of rural women reached (237.11) thousand Syrian pounds in the Al-Haffa region, which is equivalent to about 18.24 dollars in 2023. The results of measuring the level of women’s empowerment in the Al-Haffa region showed that they enjoy a moderate degree of social empowerment, with the total score for the scale reaching 60.91%. The results of measuring the development index also indicated a weak level of development in the region, as the value of the Human Development Index did not exceed (0.34). The research results also indicated that there is a moderate, positive relationship at the level (sig<0.05) between the level of social empowerment of rural women and the level of development in the Al-Haffa region.